2022
DOI: 10.24018/ejedu.2022.3.3.260
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Self-regulatory Skills and Science Students’ Practical Achievement on Rate of Chemical Reaction in Senior Secondary School, Uyo, Nigeria

Abstract: Effective engagement in practical work enables science students to acquire abilities, skills, competence and understanding of laboratory practical knowledge. The study investigates teacher self-regulatory skills in laboratory practice and students' academic achievement on the rate of chemical reaction in science. Eighty (80) science teachers and eighty (80) senior secondary science students were randomly selected from fourteen schools in Uyo Local Government Area of Akwa Ibom State, using the technique of purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…(P11) Teacher preparation has been viewed as a paradoxical cure for enhancing school curriculum, teaching, and learning while being subjected to criticisms questioning its usefulness in educating high-quality teachers for the twenty-first century. Thus, Etiubon (2015) found out that students achieved significantly better when resourceful teachers taught with e-education instructional tools. Moreover, the study of Klassen et al (2018) revealed that the most important non-cognitive qualities for effective teaching are: empathy and communication, organization and planning, and resilience and adaptability.…”
Section: Sub-theme 31 the Resourceful And Compassionate Teachermentioning
confidence: 95%
“…(P11) Teacher preparation has been viewed as a paradoxical cure for enhancing school curriculum, teaching, and learning while being subjected to criticisms questioning its usefulness in educating high-quality teachers for the twenty-first century. Thus, Etiubon (2015) found out that students achieved significantly better when resourceful teachers taught with e-education instructional tools. Moreover, the study of Klassen et al (2018) revealed that the most important non-cognitive qualities for effective teaching are: empathy and communication, organization and planning, and resilience and adaptability.…”
Section: Sub-theme 31 the Resourceful And Compassionate Teachermentioning
confidence: 95%